2004
DOI: 10.1007/s10071-004-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Transport of tools to food sites in tufted capuchin monkeys (Cebus apella)

Abstract: Tool use and transport represent cognitively important aspects of early hominid evolution, and nonhuman primates are often used as models to examine the cognitive, ecological, morphological and social correlates of these behaviors in order to gain insights into the behavior of our early human ancestors. In 2001, Jalles-Filho et al. found that free-ranging capuchin monkeys failed to transport tools (stones) to food sites (nuts), but transported the foods to the tool sites. This result cast doubt on the usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
0
26
1
3
Order By: Relevance
“…In a task where subjects have variable chances of obtaining rewards, they may decide to work or not according to their expectations of success (de Waal & Davis 2003). Capuchin monkeys may perform several exchanges in succession to obtain a final reward, they use tools sequentially to achieve a goal, they even transport tools to a food reward site (Westergaard & Suomi 1994;Westergaard et al 1998Westergaard et al , 2004Cleveland et al 2004;Drapier et al 2005). However, the goal-directed behaviours tested in the laboratory did not exceed a time scale measured in seconds.…”
Section: Discussionmentioning
confidence: 99%
“…In a task where subjects have variable chances of obtaining rewards, they may decide to work or not according to their expectations of success (de Waal & Davis 2003). Capuchin monkeys may perform several exchanges in succession to obtain a final reward, they use tools sequentially to achieve a goal, they even transport tools to a food reward site (Westergaard & Suomi 1994;Westergaard et al 1998Westergaard et al , 2004Cleveland et al 2004;Drapier et al 2005). However, the goal-directed behaviours tested in the laboratory did not exceed a time scale measured in seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Hay que señalar que respecto a las habilidades instrumentales del género Australopithecus, se poseen pocas evidencias (e. g. Semaw 2000) y se suelen poner en duda, por lo que nuestra propuesta adquiriría un gran valor heurístico en la reconstrucción de la prehistoria, algo que ya habían señalado otros autores desde distintos ámbitos científicos (Cleveland et al 2004;Goodall 1986;mcGrew 1992;pickering y domínguez-rodrigo 2010;Wrangham 1987). por razones como estas pensamos que los modelos primatológicos son un buen marco referencial para reconstruir una parte de la prehistoria.…”
Section: Conclusionesunclassified
“…este es uno de los objetivos que se pretende conseguir en este artículo: plantear la idoneidad de los modelos primatológicos para reconstruir el origen del comportamiento humano; algo, por otro lado, ya apuntado por diversos investigadores (Cleveland et al 2004;Goodall 1986;mcGrew 1992;pickering y domínguez-rodrigo 2010;Wrangham 1987). otros propósitos son los de transmitir a la investigación prehistórica española una idea clara de lo que significa la conducta instrumental y de contribuir al final, en la medida de lo posible, del mito del Homo faber, todavía persistente a pesar de la intensa crítica de las últimas décadas debido a su poco convincente peso científico (Serrallonga 1994).…”
Section: Introductionunclassified
“…Under more controlled captive conditions, Westergaard et al [1998] showed that a capuchin capable of two different tool-use tasks (hammer and insertion), could request through token exchange the appropriate tool (stone vs. probe) for whichever apparatus was baited in its cage. Cleveland et al [2004] also conducted a test for selection of an appropriate tool for different apparatuses in capuchins, but included transportation of the tool as part of the design. Tool transport has been well documented in chimpanzees [Boesch & Boesch, 1984] and Visalberghi et al [2007Visalberghi et al [ , 2009b have recently documented that wild capuchins transport stones short distances to anvils, but, at the time of the Cleveland et al [2004] study, capuchins' ability to transport tools to a specific location to obtain food in the wild was implied but not verified [Fragaszy et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Cleveland et al [2004] also conducted a test for selection of an appropriate tool for different apparatuses in capuchins, but included transportation of the tool as part of the design. Tool transport has been well documented in chimpanzees [Boesch & Boesch, 1984] and Visalberghi et al [2007Visalberghi et al [ , 2009b have recently documented that wild capuchins transport stones short distances to anvils, but, at the time of the Cleveland et al [2004] study, capuchins' ability to transport tools to a specific location to obtain food in the wild was implied but not verified [Fragaszy et al, 2004]. Further, one study of captive capuchins concluded that they were incapable of transporting tools to food [Jalles-Filho et al, 2001].…”
Section: Introductionmentioning
confidence: 99%